Experimental and Theoretical Study of Natural Convection Heat Transfer between Two Inclined Concentric Cylinders Filled With Porous Media - Abeer M. Ali (Tikrit Journal of Engineering Sciences, 2013)
Porous media have considerable importance in improvement of heat transfer and storage. This research includes an experimental and theoretical study of transient and steady state natural convection heat transfer between two inclined concentric cylinders filled with a porous medium, under condition of applying uniform heat flux on the inner cylinder and constant outer surface temperature for the outer cylinder. Glass beads was used as porous medium , the study shows that the heat dissipated ability in the inner cylinder is function of Rayligh number , and the Nusselt number increase is directly proportional with the increase in Rayligh number in the steady state . Fluent program was used to show the heat dissipation and the flow lines inside the gap between the two cylinders in the horizontal and inclined situation, the experimental results show that the nature of the heat distribution depends greatly on Rayligh number, and the angle of inclination of the cylinders. An experimental relationship between Nu&Ra was obtained under the study conditions.